Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)
fs-ref-orig: Sucha, E., SIlva, E., Batista, R. et Bouchard, L. (2014). Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec. Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa. fs-code-orig: Sucha-2014b

Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec - Sucha, E.; SIlva, E.; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)
fs-ref-orig: Sucha, E., SIlva, E., Batista, R., & Bouchard, L. (2014). Mortality in Francophone minority in Canada - A 16-year follow-up study. Mortality by socioeconomic status among canadian Francophones and Anglophones living outside Québec. Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa. fs-code-orig: Sucha-2014a

Language variables in administrative health data hosted at ICES - Batista, Ricardo; Prud'homme, Denis; Tanuseputro, Peter; Manuel, Doug (L'institut du Savoir Monfort and ICES Ottawa, 2019)
Research on linguistic minorities have revealed important disparities in Canada. Numerous analyses have identified the need for further studies looking at health status, healthcare utilization access barriers and quality of care affecting francophone living in a minority contexts (FLMCs) in Canada.1 The value and need to improve access and use of valid health information to support the planification of health and social services is well documented; however, important gaps and challenges have been recognized, which limit further progress in understanding the disparities in health and health care for some subpopulations. 2

Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.